VALENSI VERBA DAN PEMETAAN PERAN TEMATIK (THETA THEORY) PREDIKAT VERBA DWITRANSITIF DALAM KLAUSA BAHASA INDONESIA - Munariswati, Munariswati (Bahterasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study investigates verbal valency and thematic role mapping of ditransitive verb predicates in Indonesian clauses by integrating verb valency theory and Theta Theory within a corpus-based analytical framework. The objectives of this study are (1) to classify ditransitive verbs according to their lexical valency, (2) to analyze the thematic roles of each argument and their mapping on to grammatical functions, and (3) to reveal the argument hierarchy formed in ditransitive constructions. The data consist of ditransitive clauses extracted from the Indonesian Web Corpus (IndoWac), online news corpora, and Indonesian academic texts, collected using Sketch Engine. The study employs a qualitative descriptive method involving stages of valency identification, thematic role assignment (Agent, Theme, Recipient/Beneficiary), and mapping of these roles on to grammatical functions to account for argument hierarchy. The findings show that Indonesian ditransitive verbs consistently exhibit three-place valency, both lexically and derivationally. The suffix -kan is the most productive marker for valency increase and for the realization of benefactive and causative roles, whereas the sufixs -i tends to function as an argument-focus shifter without introducing new arguments. These findings confirm that argument structure and thematic role mapping in Indonesian ditransitive clauses are strongly shaped by the interaction between lexical verb meaning and derivational morphology.